Imaging of Lung Disease Associated with Connective Tissue Disease - Bartlett, Emily C.; Renzoni, Elizabeth A.; Sivarasan, Nishanth; Desai, Sujal R. (Seminars in Respiratory and Critical Care Medicine, 2022)
There is a well-known association between the connective tissue disorders (CTDs) and lung disease. In addition to interstitial lung disease, the CTDs may affect the air spaces and pulmonary vasculature. Imaging tests are important not only in diagnosis but also in management of these complex disorders. In the present review, key aspects of the imaging of CTD-reated diseases are discussed.
Keywords: connective tissue diseases; radiology; CT; high-resolution CT; lung disease